Analisis Tingkat Kesehatan Bank Menggunakan Metode RBBR di Bank Tabungan Negara Syariah - Dadang Dimyati; Mega Julia Puji Rahayu R; Badriyatul Huda; Uus Ahmad Husaeni (Jurnal Dimamu, 2022)
This study aims to find out the health level of PT Panin Dubai Syariah Bank for the period 2017-2021 using the RGEC method. The valuation factors used are Risk Profile, Good Corporate Governance, Earning and Capital factors. The object of this research is the financial statements of research used is quantitative with a descriptive approach. The type of data used in this study is secondary data. The results showed that the health level of PT Panin Dubai Syariah Bank based on Risk Profile factors gets a healthy predicate, Good Corporate Governance gets a healthy predicate, Earning gets a unhealthy predicate and Capital gets a very healthy predicate.